Dampak Tingkat Perputaran Kas, Perputaran Piutang dan Jumlah Nasabah Kredit terhadap Profitabilitas - Gede Putu Agus Jana Susila (Jurnal Ilmiah Akuntansi, 2020)
This study aims to examine the rate of cash turnover, accounts receivable turnover and the number of credit customers on profitability. The population used was 10 LPDs with use sample of 30 data in Negara district in 2016-2018. Data collection methods used in this study were observation and document record. The data analysis technique used in this study were multiple linear regression analysis. Results of the study is cash turnover rate, accounts receivable turnover and the number of credit simultaneously has a significant effect on profitability. Partially, the cash turnover rate has a positive and significant effect on profitability, receivables turnover has a positive and significant effect on profitability,  the number of credit has a positive and insignificant effect on profitability